2014
DOI: 10.12669/pjms.311.5469
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive patients’ readiness to use of mobile phones and other information technological modes for improvingtheir compliance to doctors’ advice in Karachi

Abstract: Objective:To determine the use of information technology (IT) & electronic media for improving compliance rate to doctors’ advice in hypertensive patients in Karachi.Methods:Total 400 persons (200 males & 200 females) were randomly selected in six districts of Karachi. Data was collected through a pretested questionnaire. Following was sample criteria: age above 15 years, living in Karachi and ambulatory. Persons admitted in a hospital, individuals who were doing some physical activity during survey e.g. exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
(5 reference statements)
0
4
1
Order By: Relevance
“…5 Studies from other countries also had focussed on a specific disease groups, have reported personal mobile phone ownership ranging from 61.2% to 74%. [6][7][8][9] Though, high penetration of personal mobile phones was seen in the current study (75.9%), it was comparatively lower than Bangalore study. The difference noted may be due to the fact that, Bangalore being a hub of technological boom in India, is expected to have higher access to personal mobile phone.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…5 Studies from other countries also had focussed on a specific disease groups, have reported personal mobile phone ownership ranging from 61.2% to 74%. [6][7][8][9] Though, high penetration of personal mobile phones was seen in the current study (75.9%), it was comparatively lower than Bangalore study. The difference noted may be due to the fact that, Bangalore being a hub of technological boom in India, is expected to have higher access to personal mobile phone.…”
Section: Discussioncontrasting
confidence: 56%
“…In the Bangalore study 89% preferred only call and in another study from Karachi, Pakistan among hypertensive patients, 64.6% preferred only call as a preferred option to receive health information. 4,9 In our study the proportion of people preferring only call was comparatively less and this may be due to the difference in the study population. The participants in the current study had, higher proportion of young participants, better education status and almost 40% were able to read and text message.…”
Section: Discussionmentioning
confidence: 53%
“…Potential for such partnerships is especially high in countries where there is some preliminary evidence that such interventions are feasible. Feasibility information is available from Malaysia [ 65 67 ], Iraq [ 68 ], Pakistan [ 69 ] and South Africa [ 70 ] where the e-& mHealth interventions were well accepted and study participants found them useful.…”
Section: Discussionmentioning
confidence: 99%
“…Pakistan is one of the South Asian countries where around 18 million people at the age of fifteen and above are living with hypertension. Out of these, around 70% population is even unaware about the disease status, while only 3% successfully control blood pressure with regular medication [ 4 6 ]. Multiple antihypertensive therapeutic agents are available to combat this deadly disorder, however, their high cost and life-long use of the medication along with associated multiple adverse effects ultimately results in patient unaffordability and poor-compliance [ 7 ].…”
Section: Introductionmentioning
confidence: 99%